Acetamidinium Cation to Confer Ion Immobilization and Structure Stabilization of Organometal Halide Perovskite Toward Long Life and High‐Efficiency p‐i‐n Planar Solar Cell via Air‐Processable Method. Issue 9 (4th September 2020) - Hsiao, Kai-Chi; Jao, Meng-Huan; Tian, Kuo-Yu; Lin, Ting-Han; Tran, Dinh-Phuc; Liao, Hsueh-Chung; Hou, Cheng-Hung; Shyue, Jing-Jong; Wu, Ming-Chung; Su, Wei-Fang
Abstract : Perovskite Solar Cells In article number 2000197, Wei‐Fang Su and co‐workers incorporate a cation of acetamidinium (Aa + ) into conventional perovskite layer (MAPbI3 ). The Aa + cation effectively hinders the ion migration and enhances the long‐term stability of perovskite solar cells. The champion device achieves 20.68% efficiency. More than 80% of initial power conversion efficiency is maintained after 1300 h of 85°C/85 RH% test as encapsulated.